2012
DOI: 10.1155/2012/184538
|View full text |Cite
|
Sign up to set email alerts
|

Topical Application Effect of the Isolectin Hydrogel (Cramoll 1,4) on Second-Degree Burns: Experimental Model

Abstract: This study aimed at evaluating the use of hydrogel isolectin in the treatment of second-degree burns. Twenty male rats were randomly divided into two groups (G1 = treatment with hydrogel containing 100 μg/mL Cramoll 1,4 and G2 = Control, hydrogel). After 7, 14, 21, 28, and 35 days, animals were euthanized. On the 7th day, G1 showed intense exudates, necrosis and edema. On the 14th day, G1 showed tissue reepithelialization and moderate autolysis. On the 21st day, G1 showed intense fibroblastic proliferation, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…On the other hand, development of histological tissues obtained in this study were consistent with observed by Pereira et al [ 28 ], where the reepithelialization time was lower for animals treated with isolectin hydrogel, starting around the burn edge on the 14th day, and the injuries have been completely reepithelialized in 35 days.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, development of histological tissues obtained in this study were consistent with observed by Pereira et al [ 28 ], where the reepithelialization time was lower for animals treated with isolectin hydrogel, starting around the burn edge on the 14th day, and the injuries have been completely reepithelialized in 35 days.…”
Section: Discussionsupporting
confidence: 92%
“…In present study, we observed that upon completion of wound healing few scar tissues remained in all treated rats. Scar formation in all kinds of wound healing are normal [52] and exist even after complete healing. However, the AM treated experimental group had the lowest scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…nilotica extract gel accelerates uninfected [5] or infected burn wound healing. As reported by Kumar et al (2006) [14] and Peraira et al (2012) [15], burn wounds were usually infected by bacteria gram positive like S. aureus and this infection delays wound healing. The significant burn wound healing effect of A. nilotica extract observed in the infected group associates with delay wound healing observed after wound infection by staphylococcus aureus in controls indicating that A. nilotica pods extract are responsible for an effective antimicrobial activity.…”
Section: Discussionmentioning
confidence: 86%